RENT SEEKING PADA TATA NIAGA KOMODITAS JAGUNG DI DESA PANDANSARI LOR KAB. MALANG - Andriyani, Nina; Ashar, Khusnul; Manzilati, Asfi (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2015)
Abstract This study aims 1) to determine the format of corn trade system, 2) to know the process of formation of rents on corn trading system and 3) to determine the implications of rents on the sustainability of corn farming in the village of Pandansari Lor. This study used a qualitative approach by applying research methods of phenomenology, which is the the study of the experience that comes out from awareness. The results of this study showed the corn trade system in the village of Pandansari Lor has long sequences. The corn yields of farmers had to be stored through collector that carried forward to wholesalers in the village for corn shaving. The step went to wholesalers outside the village to serve them into corn rice before reaching the final consument that is fodder company. Rent seeking also occured in those long sequences. Its either activities that occured due to manipulation of business or as utilization of the power structure. The iimplications of rent seeking likely harmed the corn farmers and multiply wealth of rent-seeking parties to the trade system.